Asuhan Keperawatan Pada Anak Dengan Demam Berdarah Dengue: Sebuah Studi Kasus - siti nurhayati; Dian Haerani (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Dengue hemorrhagic fever (DHF), a public health problem, tends to experience an increase in its incidence and spread. DHF can cause various complications: damage of the central nervous and liver, risk of shock, death. The total sample used in the target population in this study was a boy 14 years old, Islam, Javanese ethnicity, junior high school education, Indonesian language. From this study, three main nursing diagnoses were obtained, namely the risk of hypovolemia associated with capillary membrane permeability increases, the risk of bleeding is associated with thrombocytopenia, hyperthermia is associated with viremia. In the discussion of the assessment consisting of etiology, clinical manifestations, complications, diagnostic tests and medical management. In the assessment of supporting factors, namely cooperative families in providing information, while the constraints found were when he were not cooperative, didn’t care so it was difficult to get information directly.